Analisis Nilai Budaya dari Dongeng Sura Dan Baya Untuk Siswa Sekolah Dasar - Zhafira Ainun Nathifa; Badruli Martati; Muhammad Ridlwan (Journal of Practice Learning and Educational Development, 2025)
The purpose of this study was to examine the cultural values contained in the story of Sura and Baya, and its relevance as learning material for elementary school students. This folk tale contains local moral and cultural values that are important to be instilled early on in character learning. This study was conducted qualitatively descriptively by conducting content analysis on the fairy tale script. The researcher also looked at how cultural values relate to learning competencies in elementary schools. The results of the study showed that cultural values such as unity, tolerance, responsibility, and local wisdom are contained in the story of Sura and Baya. To strengthen students' cultural identity, these values can be included in Indonesian and Pancasila lessons. Therefore, the fairy tale of Sura and Baya is useful for instilling cultural awareness in elementary school students in addition to being entertainment.